The use of robots for augmentative manipulation during play activities among children with motor impairment: a scoping review. Issue 5 (27th February 2023) - Espín-Tello, Sandra Martina; Gardeazabal, Xabier; Abascal, Julio
Abstract: Purpose: To describe the extent, type, and quality of studies involving robots for augmentative manipulation during play by children with severe motor impairments (CwSMI), and to explore how they influenced children's cognitive skills and engagement. Methods: Web of Science, Scopus, PubMed & EBSCO were systematically searched for articles published until March 2021, that reported cognitive skills and/or engagement outcomes from interventions involving the use of robots in play activities, where participants included CwSMI, and full-text was available. Data extracted comprised characteristics of participants, study design, purpose of the study, outcomes assessed, collection methods, and intervention carried out (robot-environment interaction and robot used). Results: Eight mobile robots and five robotic arms were reported in the 17 included and reviewed articles. Most of them informed a positive impact on CwSMI's cognitive skills and/or engagement. However, the studies scored poorly on a five-criteria quality assessment, and only one single-case design proved strong evidence of treatment. None of the analysed interventions was an evidence-based practice. Conclusion: The use of manipulative robots during play activities may have a positive impact on the CwSMI's cognitive skills and engagement in activities. However, further studies with higher internal and external validity are needed to support stronger evidence. Implications for rehabilitation: The use of robots for augmentative manipulation during play activities may have a positive influence on the cognitive functions and the engagement in activities of children with severe motor impairments. Through manipulative robots, this population could be able to show the abilities that are hidden due to their motor impairments, and subsequently, receive educational and physical training more aligned with their real capacities and potential.